Advancing SDG 4 through TPACK-Driven Development of Technological Knowledge and Competence in Pre-Service Science Teachers - Dyah Astriani; An Nuril Maulida Fauziah; Ahmad Fauzi Hendratmoko; Laily Rosdiana; Martini Martini; Nur Hayati (Journal of Current Studies in SDGs, 2026)
Objective: The increasing complexity of 21st-century education requires pre-service science teachers to develop integrated knowledge of technology, pedagogy, and content. This study aims to examine the relationships among Content Knowledge (CK), Technological Knowledge (TK), Technological Content Knowledge (TCK), and Technological Pedagogical Content Knowledge (TPACK) in shaping pre-service science teachers’ competence to integrate technology into science instruction. Method: A quantitative approach with a cross-sectional survey design was employed. Data were collected using a valid and reliable TPACK questionnaire and analyzed through Structural Equation Modeling using SmartPLS. Result: The findings revealed that CK significantly contributed to both TK and TCK, indicating that strong content mastery supports the development of technology-related knowledge. TK also made a substantial contribution to TCK and a moderate direct contribution to TPACK. Among all examined relationships, TCK provided the strongest contribution to TPACK. These results suggest that the development of TPACK is not determined by CK alone, but is strengthened through the integration of technological and content knowledge. Novelty: The novelty of this study lies in highlighting TCK as a key mediating domain that bridges CK and TK in developing pre-service science teachers’ TPACK, thereby offering empirical evidence for designing teacher education programs that support technology-integrated science learning and contribute to quality education aligned with SDG 4.